Lifitegrast clinical efficacy for treatment of signs and symptoms of dry eye disease across three randomized controlled trials. (2nd October 2016) - Holland, Edward J.; Whitley, Walter O.; Sall, Kenneth; Lane, Stephen S.; Raychaudhuri, Aparna; Zhang, Steven Y.; Shojaei, Amir
Abstract: Objective: Report efficacy findings from three clinical trials (one phase 2 and two phase 3 [OPUS-1, OPUS-2]) of lifitegrast ophthalmic solution 5.0% for treatment of dry eye disease (DED). Research design and methods: Three 84-day, randomized, double-masked, placebo-controlled trials. Adults (≥18 years) with DED were randomized (1:1) to lifitegrast 5.0% or matching placebo. Changes from baseline to day 84 in signs and symptoms of DED were analyzed. Main outcome measures: Phase 2, pre-specified endpoint: inferior corneal staining score (ICSS; 0–4); OPUS-1, coprimary endpoints: ICSS and visual-related function subscale (0–4 scale); OPUS-2, coprimary endpoints: ICSS and eye dryness score (EDS, VAS; 0–100). Results: Fifty-eight participants were randomized to lifitegrast 5.0% and 58 to placebo in the phase 2 trial; 293 to lifitegrast and 295 to placebo in OPUS-1; 358 to lifitegrast and 360 to placebo in OPUS-2. In participants with mild-to-moderate baseline DED symptomatology, lifitegrast improved ICSS versus placebo in the phase 2 study (treatment effect, 0.35; 95% CI, 0.05–0.65; p = 0.0209) and OPUS-1 (effect, 0.24; 95% CI, 0.10–0.38; p = 0.0007). Among more symptomatic participants (baseline EDS ≥40, recent artificial tear use), lifitegrast improved EDS versus placebo in a post hoc analysis of OPUS-1 (effect, 13.34; 95% CI, 2.35–24.33; nominal p = 0.0178) and in OPUS-2 (effect, 12.61; 95% CI, 8.51–16.70; p < 0.0001). Limitations: Trials were conducted over 12 weeks; efficacy beyond this period was not assessed. Conclusions: Across three trials, lifitegrast improved ICSS in participants with mild-to-moderate baseline symptomatology in two studies, and EDS in participants with moderate-to-severe baseline symptomatology in two studies. Based on the overall findings from these trials, lifitegrast shows promise as a new treatment option for signs and symptoms of DED.